UPAYA HUKUM ATAS KERUGIAN PENUMPANG PADA TRANSPORTASI UDARA NIAGA BERJADWAL NASIONAL - Teguh Yudha Wiryawan, I Gusti Ngurah Gede; Astariyani, Ni Luh Gede (Kertha Semaya : Journal Ilmu Hukum, 2014)
The rapid development of commercial air transport currently spotted in the rights of passengers who are not properly met , as well as any flight accidents always cause harm to passengers who of course gave birth to legal issues , particularly with regard to the responsibility of the airline or carrier to passengers and the owner of the goods either sebaga the parties to the agreement as well as the transport of the consumer . The purpose of this study was to determine the setting of legal protection of scheduled commercial passenger air transportation nationwide and to determine the legal remedies that can be done when a passenger suffered a loss in national scheduled commercial air transport . This is a descriptive research analyst , and from this study it can be concluded that the need for legislation relating to the protection of the law for passenger air transportation for passengers and air transport are feeling or experiencing a loss can file a lawsuit or a claim to the airline , the settlement of a lawsuit or dispute can be reached through two channels, namely the court lines and lines outside the court.
Keywords: legal effort, air transportation